Incidence, prevalence, and causes of death of patients with autoimmune hepatitis: A nationwide register-based cohort study in Finland. Issue 9 (September 2019) - Puustinen, Lauri; Barner-Rasmussen, Nina; Pukkala, Eero; Färkkilä, Martti
Abstract: Background: Epidemiological studies of autoimmune hepatitis are scarce and often based on single centre registries. Aims: We conducted a nationwide register study of incidence, prevalence, survival, and causes of death of autoimmune hepatitis patients in Finland. Methods: Autoimmune hepatitis cases 1995–2015 were retrieved from the national database of special reimbursements for drugs costs. Data on causes of death were retrieved from Statistics Finland. Results: After incomplete registration of AIH during the first years, the incidence of autoimmune hepatitis stabilised to 1.1/100, 000 person-years (1.6 in women and 0.52 in men) in 2008–2015. The prevalence of autoimmune hepatitis at the end of 2015 was 14.3/100, 000, 23.0/100, 000 in women and 6.6/100, 000 in men. The all-cause standardized mortality ratio (SMR) of autoimmune hepatitis patients was 1.81 (95% confidence interval (CI) 1.47–2.20). The SMR was increased in all age groups and in both sexes. The SMR for hepatocellular carcinoma was 20.6 (95% CI 10.3–36.8), and for digestive diseases in overall 13.5 (95% CI 8.2–20.8), constituting mainly from autoimmune hepatitis and liver cirrhosis. Conclusion: Incidence of autoimmune hepatitis has remained stable, with clear female predominance. Autoimmune hepatitis is associated with a markedly increased risk of death with hepatocellular cancer forming the greatest risk.